Comparative Pathologic, Immunohistochemical, Ultrastructural and Molecular study of Bovine Papilloma Virus type 1 E5 Oncogene infection in Exotic and Indigenous cattle breeds - Akanbi, Olatunde Babatunde; Teifke, Jens Peter; Adedeji, Adeyinka Jeremy; Franzke, Kati; Meseko, Clement Adebajo; Daodu, Oluwafemi B.; Jegede, Henry Olanrewaju (Universitas Airlangga, 2022)
Bovine papillomavirus (BPV) induces benign tumors of cutaneous or mucosa epithelia, called papillomas or warts in cattle and generally regress without eliciting any serious clinical problems in the host, but occasionally persist and provide the focus for malignant transformation to squamous cell carcinoma. This has a negative implication in beef and hide industry. There is paucity of information on the comparative pathology and molecular detection of BPVs in different breeds of nomadic cattle. Consequently, 340 nomadic cattle grazing in Plateau state Nigeria were screened clinically for papillomatosis followed by histopathology. Lesion consistent with papillomatosis were further investigated using immunohistochemistry (IHC), Polymerase chain reaction (PCR) and electron microscopy. Twenty cattle (0.06%) of Friesian, Zebu, Muturu and White Fulani breeds had cutaneous papilloma and skin lesions of the head, neck, shoulders, legs, dorsum, lower abdomen and scrotum. However, only 16 (0.05%) cattle skin biopsy samples were consistent with papillomatosis histopathologically revealing varying degrees of hyperplastic epidermis with acanthosis and orthokeratotic hyperkeratosis. Nuclei in the granular layer of the epidermis were IHC positive for Bovine papillomavirus type I antigen while skin biopsy was BPV-1 E5 oncoprotein gene positive by PCR. Electron microscopy revealed ultrastructural changes consistent with Bovine papillomavirus infection. The distribution and severity of lesion varied in different breeds of nomadic cattle. The detection, diagnosis and characterization of papillomavirus in these cattle enabled the development of autogenous vaccine to immunized cattle. This study highlighted the comparative pathology and molecular characterization of BPVs in different breeds of nomadic cattle, which hitherto was lacking.